Design and Build a Web-Based Employee Payroll Application to Increase Efficiency at KACE Stores - Fitria; Emy Iryanie; Heldalina (MultiTech Publisher, 2025)
Toko KaCe is an SME that still uses a manual payroll system that causes errors, delays, and non-transparency. This research aims to develop a web-based payroll application to improve efficiency and accuracy. This research uses system development methods, including requirements analysis, design, development, and evaluation of PHP and MySQL-based applications. Data was collected through interviews with HR managers, manual system observations, and employee surveys after the system implementation. This research fills the gap by developing a payroll application for SMEs, which previously focused more on large companies. The results show that web-based applications can reduce errors, speed up payroll, and increase transparency with easily accessible reports. This application has proven to be effective in increasing payroll efficiency and transparency at Toko KaCe.